2019
DOI: 10.1093/hmg/ddz069
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the cross-phenotype network region of disease modules reveals concordant and discordant pathways between chronic obstructive pulmonary disease and idiopathic pulmonary fibrosis

Abstract: Chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF) are two pathologically distinct chronic lung diseases that are associated with cigarette smoking. Genetic studies have identified shared loci for COPD and IPF, including several loci with opposite directions of effect. The existence of additional shared genetic loci, as well as potential shared pathobiological mechanisms between the two diseases at the molecular level, remains to be explored. Taking a network-based approach, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Recently, a PPI network‐based approach unveiled molecular network neighborhoods for chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF), with a statistically significant region of intersection and network proximity (Halu et al, 2019). The shared network region involved 19 genes, including Rho GTPase activating protein 12 ( ARHGAP12 ) and butyrylcholinesterase ( BCHE ) as key nodes.…”
Section: Successful Applications Of Molecular Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a PPI network‐based approach unveiled molecular network neighborhoods for chronic obstructive pulmonary disease (COPD) and idiopathic pulmonary fibrosis (IPF), with a statistically significant region of intersection and network proximity (Halu et al, 2019). The shared network region involved 19 genes, including Rho GTPase activating protein 12 ( ARHGAP12 ) and butyrylcholinesterase ( BCHE ) as key nodes.…”
Section: Successful Applications Of Molecular Networkmentioning
confidence: 99%
“…The shared network region involved 19 genes, including Rho GTPase activating protein 12 ( ARHGAP12 ) and butyrylcholinesterase ( BCHE ) as key nodes. Thus, network‐based strategies may also offer a potent means to dissect genes and pathways shared between phenotypically distinct diseases, such as COPD and IPF, thus offering novel insights into pathobiological mechanisms (Halu et al, 2019). In earlier work, by mapping the seed genes onto the human interactome via the DIAMOnD algorithm (Ghiassian et al, 2015), an asthma‐associated network neighborhood was identified (Sharma et al, 2015).…”
Section: Successful Applications Of Molecular Networkmentioning
confidence: 99%
“…Such environmental stress cues as bleomycin [ 58 , 116 , 117 ], IR [ 105 , 118 , 119 ] or H 2 O 2 [ 102 , 120 , 121 , 122 ] have been shown to induce telomere DNA damage, resulting in telomere shortening. Consistent with cigarette smoking as causing pulmonary lesions by a mechanism of telomeric DDR [ 123 , 124 , 125 ], a significant number of smokers with IPF and chronic obstructive pulmonary disease (COPD) demonstrated acceleratory shortening of telomeres [ 47 , 123 , 126 ]. We demonstrated that radiation exposure, oxidative stress (such as H 2 O 2 ) or bacterial product bleomycin each trigger telomere shelterin protein TPP1 degradation in AEC2 stem cells, provoking telomere uncapping, DDR, stem cell exhaustion, fibrogenic gene expressions, and pulmonary fibrosis [ 35 ].…”
Section: Telomere Dysfunction Mediates Pulmonary Senescence and Fibrosismentioning
confidence: 99%
“…No previous associations were found for the intergenic rs76537958 at 4q32.1, while variants (LD with rs76537958: r 2 < 0.1) in RAPGEF2 have been associated with FVC in UKB Neale v2 analysis, childhood and lifetime pneumonia 22 . In addition, RAPGEF2 has been reported as a shared risk factor for both IPF and chronic obstructive pulmonary disease (COPD) in a network analysis 23 .…”
Section: Multiple Variants Associated With Lung Function and Different Organ Manifestationsmentioning
confidence: 99%